Pelaksanaan Akad Wadiah Pada Koperasi Pojok Syariah - Irma Reviana Assyarif; Inne Risnaningsih; Nurjamil Nurjamil (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Wadiah is a type of savings that is purely a depositor/customer, which must be maintained and returned at any time in accordance with mutual agreement or in accordance with the depositor/customer wishes. This wadiah contract savings is adjusted to the Presfective of DSN MUI Fatwa No.02 / DSN-MUI / IV / 2000 concerning wadiah savings. Therefore, this study aims to determine the application of the wadiah contract, the conformity of the DSN MUI Fatwa Presfective No.02 / DSN-MUI / IV / 2000, and find out the efforts made by the Sharia Pojok Cooperative to comply with the Fatwa Prefectives of the National Sharia Council of the Indonesian Ulema Council. The research method used is to use a qualitative descriptive approach. Data collection obtained through observations to the Sharia Pojok Cooperative an also interviews with informants and literature studies to be able to describe the implementation of the wadiah contract. The results of this study are known that the implementation of the wadiah agreement in the Sharia Pojok Cooperative has one discrepancy with the Prefectives of the Fatwa of the National Sharia Council of the Indonesian Ulema Council No.02 / DSN-MUI / IV / 2000 concerning Savings, namely the Sharia Pojok Cooperative hinting at the bonus at the beginning of the contract of 4%.